Wealth of two nations: The U.S. racial wealth gap, 1860-2020 - Ellora Derenoncourt; Chi Hyun Kim; Moritz Kuhn; Moritz Schularick (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
The racial wealth gap is the largest of the economic disparities between Black and white Americans, with a white-to-Black per capita wealth ratio of 6 to 1. It is also among the most persistent. In this paper, we construct the first continuous series on white-to-Black per capita wealth ratios from 1860 to 2020, drawing on historical census data, early state tax records, and historical waves of the Survey of Consumer Finances, among other sources. Incorporating these data into a parsimonious model of wealth accumulation for each racial group, we document the role played by initial conditions, income growth, savings behavior, and capital returns in the evolution of the gap. Given vastly different starting conditions under slavery, racial wealth convergence would remain a distant scenario, even if wealth-accumulating conditions had been equal across the two groups since Emancipation. Relative to this equal-conditions benchmark, we find that observed convergence has followed an even slower path over the last 150 years, with convergence stalling after 1950. Since the 1980s, the wealth gap has widened again as capital gains have predominantly benefited white households, and income convergence has stopped.
Keywords: J15; N31; N32; 330; Racial inequality; income and wealth inequality; Vermögensverteilung; Schwarze Menschen; Ethnische Gruppe; USA